Vibration isolation with clutch disk pre-damper mechanism for the idle rattle phenomenon - Yucesan, Alisan; Sezer, Semih (SAGE PUBLICATIONS LTD, 2018)
In this paper, the influence of clutch disk pre-damper mechanism constituents on the idle rattle phenomenon was investigated with an analytical model containing a new time-varying gear mesh stiffness function. Comparing experimental results to simulation results for the same excitation input was the key implementation for the validation of proposed model. The engine speed fluctuations represented in the simulation was imported from a speed measurement of a diesel engine in the test bench.
Keywords: Engine speed fluctuations; torsional vibrations; gear rattle; clutch pre-damper mechanism; idle rattle; powertrain vibrations; time-varying gear mesh stiffness function; OIL SQUEEZE; TEETH; MODEL; Acoustics; Engineering; Mechanics